Appendix 3: Chronology of Major Sounds Laws - Nesset, Tore (Septentrio Educational, 2015)
In chapters 10–13, the sound laws were not described in strict chronological order, but this appendix will help you to establish the relative and absolute chronologies of the major changes. For Pre-Slavic and Common Slavic, the overviews in sections 18.1 and 18.2 are based on Shevelov 1964: 633–634. The chronologies for Old Rusian in section 18.3 are based on Kiparsky 1963: 153–154, as well as Gorškova and Xaburgaev 1981 and Ivanov 1983. You are advised to take the chronologies with more than a grain of salt, since data are often sparse and sometimes conflicting. Unsurprisingly, therefore, different handbooks provide different dates.